Genotype x environment interaction and stability analyses of yield of upland cotton (Gossypium hirsutum L.) in central Sudan - Ahmed1, Hassan S.; Mohamoud, Mohamoud A.; Ibrahim, Abu Elhassan S.; Suliman, Abbas M. (Gezira Journal of Agricultural Science; Vol 17 No 1 (2019), 2019)
Seed cotton yield stability of genotype over environments is a useful parameter for recommending cultivars for known cropping conditions. Fifteen upland cotton inbred lines and the check (commercial cultivar Hamid were evaluated. over two consecutive seasons (2013/14 and 2014/15) at three locations,  Rahad, Gezira and Sennar Research Station of the Agricultural Research Corporation, Sudan. A randomized complete block design with four replicates was used. The objective was to assess the genotype by environment interaction and stability of seed cotton yield. The mean squares due to environment were significant while genotype and genotype x environment interaction were highly significant for seed cotton yield. Significant differences among genotypes for the studied characters were found in almost all seasons, indicating that these cotton genotypes were highly variable for the characters studied and, therefore, expected to respond to selection. The interaction effects of genotype x location were significant for all traits indicating that genotypes responded differently to different environments. Statistical models of stability analysis, i.e. Eberhart and Russel model as well as the additive main effect and multiplicative interaction (AMMI), indicated that genotypes RS-5, R-96, R-231, R-43 and R-1 revealed good stability and high seed cotton yields across environments. In conclusion, and based on stability parameters, genotypes R-6, R-40, R-231, and R-43 are recommended for further testing over a range of environments to examine their yield stability and suitability for large field production.  يعتبر ثبات الانتاجية للقطن الزهرة من أفضل الطرق للتوصية بزراعة الاصناف حسب الظروف المحصولية لكل صنف. تم اختبار 15 سلالة نقية من القطن الأكالا ( Gossypium hirsutum L.)  بالأضافة الي الصنف حامد المنزرع تجاريا بالسودان في موسمي 14/2013  و 15/2014 في محطة بحوث الرهد و محطة بحوث الجزيرة و محطة بحوث سنار, هيئة البحوث الزراعية (ARC), السودان. استخدم تصميم القطاعات العشوائية الكاملة بأربعة مكررات. هدفت الدراسة لتقويم التفاعل الوراثي والبيئ وثبات درجة انتاجية القطن زهرة. أظهرتحليل التباين فروقات معنوية مع البيئات بينما أظهرت السلالات وتفاعل السلالات مع البيئات لانتاجية القطن زهره فروقات معنوية عالية. أيضا أظهرة الدراسة فروقات معنوية لمعظم الصفات التي درسة في كل موسم, وهذا يشير الي وجود فروقات عالية بين سلالات القطن التي درست, عليه يمكنها الاستجابة للانتخاب. أوضح التحليل الاحصائي ل Eberhart and Russel model (1966)   و (AMMI) أن الطرز RS-5 و R-96 و R-231 وR-43 و R-1 أظهرت درجة ثبات وانتاجية عالية في كل البيئات . خلاصة البحث واستناداً علي متوسط الأداء وثبات الانتاجية يوصى باختبار ثبات انتاجية الطرز الوراثية R-6 وR-40 و R-231و R-43 في عدة مواقع ومواسم للتأكد من نتائج هذه الدراسة والاستفادة منها في توصية باجازة بعض هذه الطرز لتناسب الظروف البيئية في السودان